Evolution, present status and issues concerning small tank systems in Sri Lanka [Small tanks in Sri Lanka: evolution, present status and issues] - Panabokke, Christopher R.; Sakthivadivel, Ramaswamy; Weerasinghe, A.D. (International Water Management Institute, 2002)
The core of this study involved an examination and analysis of certain key features of the traditional small tank cascade systems: a) the location and design of the systems in the past b) the hydro-system which considers the overall hydrological balance and groundwater conditions c) maintenance and tank use d) tank management and integration with local farming systems